Effect of carnitine on muscular glutamate uptake and intramuscular glutathione in malignant diseases - Breitkreutz, Raoul; Edler, Lutz; Holm, Eggert; Dröge, Wulf (British journal of cancer, 2000)
Abnormally low intramuscular glutamate and glutathione (GSH) levels and/or a decreased muscular uptake of glutamate by the skeletal muscle tissue have previously been found in malignant diseases and simian immunodeficiency virus (SIV) infection and may contribute to the development of cachexia. We tested the hypothesis that an impaired mitochondrial energy metabolism may compromise the Na+-dependent glutamate transport. A randomized double-blind clinical trial was designed to study the effects of L -carnitine, i.e. an agent known to enhance mitochondrial integrity and function, on the glutamate transport and plasma glutamate level of cancer patients. The effect of carnitine on the intramuscular glutamate and GSH levels was examined in complementary experiments with tumour-bearing mice. In the mice, L -carnitine treatment ameliorated indeed the tumour-induced decrease in muscular glutamate and GSH levels and the increase in plasma glutamate levels. The carnitine-treated group in the randomized clinical study showed also a significant decrease in the plasma glutamate levels but only a moderate and statistically not significant increase in the relative glutamate uptake in the lower extremities. Further studies may be warranted to determine the effect of L -carnitine on the intramuscular GSH levels in cancer patients.